Baby Incubator Based on PID Control With Kangaroo Mode (Kangaroo Mode and Humidity) - Nur Fildzah Hidayati; Endro Yulianto; Abd Kholiq (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2019)
Baby Incubator is one of the electromedical equipment used to provide protection to premature babies or low birth weight. Baby care in the baby incubator causes separation of mother and baby. A new innovation in the care of premature babies who bring their babies and mothers closer is Kangaroo Method Management (PMK). Kangaroo method treatment aims to create emotional attachment to the baby, so that the mother will confidently take care. The research and manufacture of this module uses a method of treating baby incubator by adding a reading of the room temperature when the kangaroo mode runs at a setting of 34 ° C - 37 ° C with the effect of room temperature at 18 ° C, 24 ° C, and 30 ° C and setting the humidity control automatically by measuring at a temperature of 32 ° C, then measuring the results immediately. Sensors used to detect temperature are LM35 sensors and sensors used to detect humidity using DHT22. Based on the measurement results obtained uncertainty values ​​on the measurement of humidity 2.1, the measurement of temperature stability can be seen from the results of the graph which shows that the room temperature is not too influential at the temperature of the baby incubator. This study has shown the development of baby incubators to help mothers who have babies born prematurely so that they can have a good bond with how to treat skin to skin. This study has proven that its accuracy is appropriate to be used to stabilize the condition of babies born prematurely and help to treat PMK in some hospitals. In the future, this research can be made and used in small clinics in villages at low costs.